The role of the penitentiary library in the social rehabilitation of inmates of the "Puente Grande" Penitentiary Complex, Jalisco, Mexico - Ochoa-García, Julián; Martínez-Camacho, Humberto (Facultad de Filosofía y Letras, Universidad de Buenos Aires, 2020)
This work analyzes the influence that libraries have within penitentiary centers in relation to the social rehabilitation of their inmates from the perspective of those responsible for libraries or reading spaces within the prisons that compose the "Puente Grande" Penitentiary Complex, in the State of Jalisco, Mexico, carrying out a questionnaire that was applied to those in charge of the libraries in the four centers that are part of this complex, in which the library concept  and its influence on social readaptation from a qualitative perspective,  the analysis of the services provided and, finally, the care and training of users. Among the main results, the following are highlighted: 1) the importance of reading and training activities as an instrument for social reinsertion, 2) the lack of professional training for those in charge, of the libraries 3) the deficiency in terms of physical and technological resources.